Discovery of Hishimonus diffractus Dai, Fletcher & Zhang, 2013 (Hemiptera: Auchenorrhyncha: Cicadellidae) in Europe, with remarks on previously recorded species of the genus - Bella, Salvatore; Aguín-Pombo, Dora; Aguiar, António M.f.; Kunz, Gernot; Miralles-Núñez, Adrià; Foster, Stuart; Sánchez-García, Iñigo; Wilson, Michael R.; D’urso, Vera (Zootaxa, 2022)
During recent surveys on leafhoppers in urban and agroecosystem areas in Europe the Oriental Hishimonus diffractus Dai, Fletcher & Zhang, 2013 (Hemiptera, Cicadellidae) has been found. This species, described from China and Thailand, is recorded here for the first time from Europe in the following countries: France, Portugal (Madeira), Spain, Gibraltar, United Kingdom, and Italy (Sicily). H. diffractus has been found associated with Jasminum and Olea (Oleaceae), Citrus (Rutaceae), Pittosporum (Pittosporaceae), Rubus (Rosaceae), Nerium (Apocynaceae) and Vitis (Vitaceae). Presence of the adults, morphological features, and some biological notes are provided to H. diffractus. Furthermore, Hishimonus hamatus Kuoh, 1976 is here reported for the first time in Spain and France. All Hishimonus species introduced in Europe are considered, and their economic importance discussed. Details on the first record and country in Europe, origin area, current distribution and host plants are given for each species.